Distributed maximum correntropy filtering for a class of multi-rate systems over sensor networks - Liu, Yang; Wang, Zidong; Hu, Jun; Chen, Yun; Dong, Hongli (Information fusion, 2026)
•The distributed maximum correntropy filtering problem is investigated.•A class of multi-rate systems over sensor networks is considered.•The sampling periods are allowed to be different.•A novel correntropy-based filtering performance index is constructed.•The desired filter gain is calculated using a fixed-point algorithm. In this paper, the distributed maximum correntropy filtering problem is investigated for a class of multi-rate systems over sensor networks. The system under consideration is monitored by a sensor network whose sensors are permitted to have different sampling periods. The maximum correntropy criterion is employed to handle the non-Gaussian noises effectively. Given the distributed nature and the asynchronous sampling of the sensor network, a novel filtering performance index based on the correntropy is constructed for each node in the sensor network. To maximize this correntropy-based index, the desired filter gain at each time step is calculated using a fixed-point algorithm. Sufficient conditions for ensuring the convergence of the fixed-point method are established. Finally, the efficacy of the proposed filtering scheme is demonstrated through a target tracking example.